Plasma leptin concentration and change in bone density among elderly men and women: the Hertfordshire Cohort Study. - Dennison, E; Syddall, H; Fall, C; Javaid, M; Arden, N; Phillips, D; Cooper, C (2004)
Several studies have shown an association between circulating leptin concentration and bone mineral density. but most studies are cross-sectional in design and report findings in women only. We per-formed a population-based longitudinal study relating baseline plasma leptin concentration to bone mass at the lumbar spine and femoral neck and to change in bone density at these sites over four years in a cohort of 302 men and women aged 60 75 years born and still resident in Hertfordshire, UK. Baseline plasma leptin concentration was strongly positively correlated with body mass index (men: r = 0.71, P 0.0001; women: r = 0.79, P < 0.0001) and with bone mineral content,bone mineral density, and volumetric bone mineral density at all sites (r = 0.24-0.36, P < 0.001) in both sexes: associations with change in bone density were markedly weaker and inconsistent. Adjustment for adult lifestyle determinants of osteoporosis made little difference to our results, but the associations of leptin with bone mass were no longer significant after adjustment for body mass index. These results suggest that the relationship between plasma leptin and bone mass is similar in men and women and that it is mediated through the strong association of both variables with adiposity, rather than through a direct association of leptin on bone cell function.